Odpowiedzi

2009-10-01T21:02:03+02:00
Razy zastąpię znakiem "*"
oraz odjąć "-"

5 2/5 odjąć 2/3 razy (7,2- (-1 4/5))=
5 2/5 - 2/3 * (7,2 - (-1 4/5))=
5 2/5 - 2/3 * (7,2 + 1,8)=
5 2/5 - 2/3 * 9 =
5,4 - 6 = -0,6

8 3/5 odjąć 3/5 razy ( 8,4 ( -6 3/5))=
nie napisałeś znaku w nawiasie
Najlepsza Odpowiedź!
2009-10-01T21:02:55+02:00
5,4-2/3(7,2+2,8)=5,4-2/3(10)=5,4-20/3=5,4-6,7=-1,3
8,6-3/5(8,4-12,6)=8,6-3/5(-4,2)=8,6+2,52=11,12
2009-10-01T21:04:20+02:00
5 2/5 odjąć 2/3 razy (7,2- (-1 4/5)) = 5⅖-⅔*(7,2+1,8) = 5⅖-⅔*9 = 5⅖-6 = -⅗ = -0,6



8⅗ - ⅗ * ( 8,4 (-6,6)) = 8⅗-⅗*1,8 = 8⅗-0,6*1,8 = 8,6-1,08 = 7,52
Nie ma znaku w nawiasie, potraktowałam to jako odejmowanie